Acoustic enhancement of sleep slow oscillations in mild cognitive impairment. Issue 7 (1st July 2019) - Papalambros, Nelly A.; Weintraub, Sandra; Chen, Tammy; Grimaldi, Daniela; Santostasi, Giovanni; Paller, Ken A.; Zee, Phyllis C.; Malkani, Roneil G.
Abstract: Objective: Slow‐wave activity (SWA) during sleep is reduced in people with amnestic mild cognitive impairment (aMCI) and is related to sleep‐dependent memory consolidation. Acoustic stimulation of slow oscillations has proven effective in enhancing SWA and memory in younger and older adults. In this study we aimed to determine whether acoustic stimulation during sleep boosts SWA and improves memory performance in people with aMCI. Methods: Nine adults with aMCI (72 ± 8.7 years) completed one night of acoustic stimulation (stim) and one night of sham stimulation (sham) in a blinded, randomized crossover study. Acoustic stimuli were delivered phase‐locked to the upstate of the endogenous sleep slow‐waves. Participants completed a declarative recall task with 44 word‐pairs before and after sleep. Results: During intervals of acoustic stimulation, SWA increased by >10% over sham intervals ( P  < 0.01), but memory recall increased in only five of the nine patients. The increase in SWA with stimulation was associated with improved morning word recall ( r  = 0.78, P  = 0.012). Interpretation: Acoustic stimulation delivered during slow‐wave sleep over one night was effective for enhancing SWA in individuals with aMCI. Given established relationships between SWA and memory, a larger or more prolonged enhancement may be needed to consistently improve memory in aMCI.